A note on minke whales (Cetacea: Balaenopteridae) in Uruguay: strandings review - Juri, Eduardo; Valdivia, Meica; Simoes-Lopes, Paulo Cesar; Le Bas, Alfredo (J. Cetacean Res. Manage., 2020)
The minke whale is the smallest of the living rorquals and is widely distributed in the tropical, temperate and polar waters of both hemispheres. In the western Southwest Atlantic Ocean there are two currently recognised species, the dwarf form of the common minke whale, Balaenoptera acutorostrata unnamed subsp. and the Antarctic minke whale B. bonaerensis. All stranding records and collected specimens of minke whale on the coast of Uruguay were reviewed and analysed. Between 1962 and 2018, 33 records were gathered in a non-systematic way, 22 specimens of B. acutorostrata and 11 of B. bonaerensis. It was found that most animals were discovered alive or recently dead and assigned as neonates/young calves. This supports the hypothesis that Uruguayan coasts are part of an important region for reproduction and breeding for the species.